Edital de fomento das feiras de ciências: uma análise dos resultados da participação do estado de Mato Grosso do Sul - Gonçalves, Joshua Augusto Alves (2023)
This study aims to present the effect of science fairs and map these results in the state of Mato Grosso do Sul. Science fair actions are responsible for stimulating scientific research in basic education and bringing science to different regions of the country. Initially, it was necessary to investigate the portal from the CNPq website to understand the data made publicly available. Starting from the documentary analysis of the CNPq Science Fairs and Scientific Exhibition Promotion Notices, the results of the state of Mato Grosso do Sul were mapped, through the annals of events published from 2011 to 2022. Science fairs may or may not receive financial support from public bodies, which requires, as with any public policy, to make their results and impact available to society. The study points to the difficulty in presenting correct and easy-tounderstand data for the population. However, there is already concern among the responsible bodies to improve data dissemination. The research also points to the importance of the fair notice as a complement to other policies to encourage scientific research in basic education, however it was not possible to identify the impact that the fair notice can achieve, due to the lack of clear information, complete data, standardization and dissemination of information, which undermined the possibily to carry out an impact assessment for this public policy. Still, in the data mapped in the state of Mato Grosso do Sul, it is possible to find relevant results, with the production of several research projects being carried out by a good number of teachers and students, with the participation of different educational institutions, cities and states, in all areas of knowledge.